Application of the Professional Psychological Quest in the Professional Training of Police Officers - N. E. Miloradova; N. Ye. Tverdokhliebova (Law and Safety)
The results of the analysis of foreign and domestic approaches to the interpretation and understanding of quest technologies are presented. It is noted that in order to create the proper conditions for the formation of future police officers professional competence, motivational focus on positive personal changes and the desire for professional self-development, it is advisable to use the possibilities of innovative teaching technologies, in particular, trainings and quests. During such classes, participants have the opportunity to learn how to quickly make the right decisions within the limits of their professional competence, applying the obtained theoretical knowledge, as well as to master and consolidate the necessary skills. The educational quest is highlighted as a separate form of design technologies. The features of the developed professional-psychological police quest with elements of the training "Features of the district police officer’s activities" are revealed, its consistent stages are characterized: organizational and preparatory, implementation and final. It is noted that the basis of the police quest is the situational method, the content of which is aimed at mastering the algorithm of actions by the cadets associated with the implementation of the service tasks of the police. It has been revealed that the use of a professional-psychological police quest is an active form of group work and provides the use of set measures aimed at increasing the level of professional training of police officers, developing and changing the structure of interpersonal relations, educational and professional motivation, and contributes to the self-realization of the individual within the professional space. The authors emphasize the advisability of using a police quest, which contributes to the increase of professional competence level due to the increase of the study time amount allocated for practical work, the independent acquisition and use of new knowledge and skills in practice, making the right decisions within the framework of their professional competence, and well-coordinated teamwork.